Seasonality of phytoplankton biomass and composition on the Cape Canaveral shelf of Florida: Role of shifts in climate and coastal watershed influences - Stelling, Ben; Phlips, Edward; Badylak, Susan; Landauer, Leslie; Tate, Mary; West-Valle, Anne (Frontiers in Ecology and Evolution, 2023)
Seasonal patterns of phytoplankton biomass and composition in the inner continental shelf off Cape Canaveral on the east coast of Florida were examined for a six-year period (2013-2019). In situ water samples were collected and analyzed for chlorophyll a, phytoplankton biomass and composition, along with water quality parameters. Regional satellite data on chlorophyll a, and temperature was also obtained from NASA. Average chlorophyll a values over the study period ranged from 0.63 ± 0.03 µg L-1 in the summer to 2.55 ± 0.10 µg L-1 in the fall. Phytoplankton community composition also showed seasonal differences, with persistent dominance by picoplanktonic cyanobacteria in the summer, but mixed dominance by picocyanobacteria and dinoflagellates in the fall. Seasonal differences were attributed to a shift in predominant seasonal wind directions, which drive water along the coast from the north in the fall and winter, but from the south in the spring and summer, including eddies and upwelling from the Gulf Stream. Water masses moving along the Florida coast from the north are influenced by nutrient and phytoplankton-enriched inputs from estuaries along the north coast of Florida, explaining the higher phytoplankton biomass levels on the Cape Canaveral shelf in the fall and winter. Seasonal patterns observed in this study demonstrate the importance of allochthonous influences on phytoplankton biomass and composition, and highlight the potential sensitivity of phytoplankton communities to continuing cultural eutrophication and future climate changes, including the frequency and intensity of tropical storms, and alterations in discharges from land.